2017
DOI: 10.1080/00140139.2017.1408857
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of identification of low or high risk lifting during standardised lifting situations

Abstract: The aim was to classify lifting activities into low and high risk categories (according to The Danish Working Environment Authority guidelines) based on surface electromyography (sEMG) and trunk inclination (tri-axial accelerometer) measurements. Lifting tasks with different weights, horizontal distance and technique were performed. The lifting tasks were characterised by a feature vector composed of either the 90th, 95th or 99th percentile of sEMG activity level and trunk inclinations during the task. Linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…We have previously shown that the intra-day reliability for sEMG during lifting tasks is acceptable in laboratory conditions [26]. Furthermore, the method for detecting events of the lower back and shoulder based on sEMG and IMU from the upper back has shown high accuracy in a laboratory setng [25].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that the intra-day reliability for sEMG during lifting tasks is acceptable in laboratory conditions [26]. Furthermore, the method for detecting events of the lower back and shoulder based on sEMG and IMU from the upper back has shown high accuracy in a laboratory setng [25].…”
Section: Discussionmentioning
confidence: 99%
“…The analyses for detecting the events are described in detail elsewhere [25]. In short, the sEMG segments corresponding to the references lifts and the MVC trials were extracted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations